Role of twin and anti-phase defects in MnAl permanent magnets. (1st June 2017) - Bance, Simon; Bittner, Florian; Woodcock, Thomas G.; Schultz, Ludwig; Schrefl, Thomas
Abstract: We quantify and explain the effects of both anti-phase boundaries and twin defects in as-transformed τ-MnAl by carrying out micromagnetic simulations based closely on the results of microstructural characterization. We demonstrate that magnetic domain walls nucleate readily at anti-phase boundaries and are strongly pinned by them, due to anti-ferromagnetic coupling. Likewise, twin boundaries reduce the external field required to nucleate domain walls and provide strong pinning potentials, with the pinning strength dependent on the twinning angle. The relative strengths of the known twin defect types are quantified based on the anisotropy angles across their boundaries. Samples that have undergone heat treatment are imaged using electron back-scatter diffraction. The precise crystallographic orientation is mapped spatially and converted into a number of realistic finite element models, which are used to compute the effects of large concentrations of twin domains in a realistic morphology. This is shown to have a negative effect on the remanence coercivity and squareness. The maximum energy product ( B H ) max is therefore significantly lower than the theoretical limit of the material and much lower than MnAl permanent magnets that have been further processed to remove twin defects. The knowledge gained in this study will allow the optimization of processing routes in order to develop permanent magnets with enhanced magnetic properties. Graphical abstract: Image 1